Analyzing the Intrinsic Links and Common Therapeutic Targets between Diabetic Foot Ulcers and Liver Disease through Bioinformatics - Wenbo Li; Xudong Xin; Tianyi Shen; Zhenhao Zhang; Jihua Wei (Medicine Insights, 2026)
Background. Diabetic foot ulcer (DFU) is a critical and prolonged complication of diabetes associated with high disability and mortality rates. Lipid metabolism disorders resulting from liver diseases are a key etiology in the development of diabetes mellitus and diabetic foot. Currently, there are no effective therapeutic targets or medications for treating DFU in combination with liver diseases such as nonalcoholic fatty liver disease (NAFLD)/nonalcoholic steatohepatitis (NASH) and liver cirrhosis (LC). The intrinsic links between the pathogenesis of DFU and these liver conditions have yet to be fully elucidated. Methods. We explored the molecular networks associated with DFU and NASH, as well as DFU and LC. Datasets were downloaded from the Gene Expression Omnibus (GEO) database and differentially expressed genes (DEGs) were identified. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were performed. Protein-protein interaction (PPI) networks were constructed using the STRING database, and hub genes were identified. The co-expression framework of hub genes was analyzed, and a mRNA-miRNA-TF regulatory network was constructed. The hub genes were validated, and medication prediction and molecular docking analyses were conducted. The causal link between NAFLD and DFU was studied utilizing Mendelian randomization. Results. In DFU and NASH, 294 common DEGs were identified, with four hub genes (FOS, PTGS2, SOCS3, and CD274) associated with inflammatory, immune, and metabolic responses. In DFU and LC, 347 common DEGs were identified, with six hub genes (FOS, PTGS2, CD8A, CD44, CXCL8, and SPP1) linked to inflammatory responses, metabolic processes, and cytokine receptor interactions. Our study suggests that oxygen therapy could serve as a viable therapeutic approach for managing DFU in patients with concurrent NASH. Simvastatin, a classic lipid-lowering medication, shows potential as an effective treatment for combined with NASH or LC due to its strong binding affinity with identified hub genes. Discussion. Understanding the networks and central genes is essential for advancing our comprehension of the diverse complexities associated with diabetes and promoting the advancement of potential therapeutic strategies. Targeting these hub genes and their associated signaling pathways could provide new treatment strategies for DFU combined with NASH or LC, offering a solid theoretical foundation for future therapies.